Investigation of the Welding Workers\' Exposure to Manganese Fume in a Factory in Amol, Iran - Mahmoud Mohammadyan; Mohsen Gorgani firouzjaei; Jamshid Yazdani charati; Milad Pouransari; Shahram Eslami; Razieh Yoosefinejad; Mohammadreza Zarei (Mazandaran University of Medical Sciences, 2021)
Introduction and Purpose: Workers' exposure to manganese fumes emitted from the welding Process can lead to various ranges of diseases. This study aimed to investigate the concentration of manganese fume in the respiratory area of workers working at an industrial shed manufacturing factory in Amol, Iran. Methods: This descriptive-analytical and cross-sectional study was conducted on the welders working at an industrial shed manufacturing factory in Amol, Iran (case group; n=35) and employees of administrative departments (control group; n=35). Inhalable Particles concentration and manganese concentration in welding fumes were measured using the NIOSH-0600 and NIOSH-7300 standard methods, respectively. Data analysis was Performed by SPSS software (version 25) using descriptive (mean and standard deviation) and analytical statistical methods (chi-square test, Spearman's rank correlation coefficient, and regression testing). Results: The mean exposures of welders to inhalable Particles and manganese in welding fume were 2.4±1.2 and 0.15±0.83 mg/m3, respectively. The maximum and minimum concentrations of inhalable Particles and manganese in welding fumes were 6 and 0.36 mg/m3, as well as 0.7 and 0.04 mg/m3, resPectively. There was a significant relationship between average Particle concentration and manganese concentration in welding fume among the two groups of maximum and minimum exposure limits. Moreover, a significant association was observed between the concentration of inhalable Particles and the concentration of manganese in welding fumes (P<0.001). Conclusion: The exposure of all welders to manganese welding fume exceeded the allowable limit. Therefore, technical, engineering, and management control measures are recommended to reduce exposure to manganese.